(untitled) - Hamacher, V. Carl (New York, 1996)
The first seven chapters cover the basic principles of computer orgasation , operation, and performance, using the PowerPC and 68000 as major examples. The remaining three chapters deal with other commercial computer examples, peripheral devices, and large computer systems.
Keywords: Computer organisation